Identification and Pathogenicity of Phytopathogenic Bacteria Associated with Soft Rot Disease of Girasole Tuber - Mamdoh Ewis ISMAIL; Montaser Fawzy ABDEL-MONAIM; Yasser Mahmoud MOSTAFA (Notulae Scientia Biologicae, 2012)
During 2010-2011 growing seasons six bacterial isolates were separated from naturally infected girasole plants tubers (Helianthus tuberosus L.) cv. Balady, showing soft rot, collected from experimental Farm of the Faculty of Agriculture, in El-Minia University, Egypt. Pathogenicity tests showed various virulence for the bacteria isolated from girasole tubers, found pathogenic. These organisms were characterized as rod-shaped, Gram negative, ?-methyl-d-glucoside medium, reducing substances from sucrose, phos, phatase activity and deep cavities on pectate medium. Otherwise, diagnostic tests suggested that the pathogen was Erwinia carotovora ssp. carotovora. The isolated bacteria caused soft rot of wounded tubers when inoculated into tissues. The bacterial isolates were compared for their degree of pathogenicity as well as for differences in specific symptoms, induced in different hosts. The tested isolates could infect several host ranges, such as fruits of apricot, apple, olive, lemon, squash, eggplant and potato tubers, bulbs and garlic and onion cloves, roots radish, carrot, sweet potato and rape. On the other hand, no symptoms were exhibited on pods of bean and cowpea, faba bean, fruits of pepper and tomato. The extracts of experimentally diseased girasole tubers were active in pectinase and also in caboxymethyl cellulose at pH 6 compared to enzyme activities in healthy tissues. Also, the isolated bacteria increased the total and reducing sugars in infected tissues.